ESTIMASI PENYEBARAN COVID-19 DI INDONESIA MENGGUNAKAN MODEL PERTUMBUHAN LOGISTIK DENGAN R - Khoiroh Alfiana; Ade Ima Afifa Himayati; Muhammad Faudzi Bahari; Azma Rosyida (Universitas Muhammadiyah Kudus, 2020)
Confirmed cases of COVID-19 in Indonesia are current increasing. The cases are spreading at an exponential rate and soon be reached at a peak then decreasing the day after until the daily confirmed cases equal to zero. Some mathematics models can help estimate the spreading of COVID-19 in Indonesia, such as logistic growth model. In this research, the logistic growth model used to predict the final size then compared the numbers with the confirmed data. The result indicates that the logistic model suits to describe the growth cases of COVID-19 in Indonesia. Estimation of the final size will be approximately cases until this December.